Seed production: Perspective from the Brazilian private sector - Santos Filho, L.F. (International Center for Tropical Agriculture, 1996)
Brachiaria cultivars developed by forage research programs are delivered to commercial livestock producers through the vehicle of seed. Over the past 15-20 years, a large, dynamic industry has developed in Brazil for the production of Brachiaria seed. This paper describes the history of this industry, its magnitude and projections for the future. The see production technology that has evolved in Brazil is briefly described. Constraints to the commercial development and exploitation of Brachiaria, as perceived from the private sector, are listed. The priorities of the private sector do not always coincide entirely with those of public sector researchers; a plea is therefore made for closer cooperation between private and public sector efforts to develop and exploit these forage grasses to benefit tropical livestock production.